Evaluation of The Coverage of The Covid-19 Vaccine and The Contribution of Patriarchal Culture in Influence it on Nias Island - Wasiyem Wasiyem; Zata Ismah; Meutia Nanda; Tri Bayu Purnama (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The President targets that by the end of 2021, the number of people vaccinated will be 70%. Meanwhile, in October 2021, the target for achieving dose 1 had only reached 43.13%. The implementation of the Covid-19 vaccination in Indonesia, especially in several outer islands of Sumatra, still faces several obstacles in the community. These obstacles include difficult storage and distribution of vaccines in island areas far from the provincial center. This research aims to evaluate the coverage achievement figures, the Covid-19 vaccine and the contribution of Partiarchy culture in Nias Island. This research is a mixed methods research with explanatory sequential design. The sampling for quantitative research using the categorical proposition formula were 338 samples and for qualitative research were 22 informant. Thus, the total number of people studied in this reasearch was 410 people over 15 years of age who permanently live on Nias Island, North Sumatra. Data collection in this research is primary data by questionnaires and in-depth interviews. Data anlaysis for quantitative data was carried out in 2 ways, namely univariate and bivariate (chi-square) analysis. Meanwhile, analysis for qualitative data uses content analysis. The research results showed that the coverage rate of the Covid-19 vaccine on Nias Island in this study was lower than reported in the Indonesian Ministry of Health data with details of dose 1 (87.9%), dose 2 (75%), and dose 3 (16.2%). The contribution of Partiarchy culture to the acceptance of the Covid-19 vaccine on Nias Island is in the form of families who are extremely partiarchy having a greater chance of not getting the vaccine than those who are normally Partiarchy. If a father (from a patriarchal family) does not want the vaccine, the whole family will follow the father's decision even if there are differences in the opinions of other family members, and vice versa. Recommendations from the results of this research are to increase the coverage rate of the Covid-19 vaccine, requiring special attention and approaches to radical partyararchy families. Keywords : Covid-19 Vaccine, Patriarchy culture